Multiparametric Whole-body MRI with Diffusion-weighted Imaging and ADC Mapping for the Identification of Visceral and Osseous Metastases From Solid Tumors - Jacobs, Michael A; Macura, Katarzyna J; Zaheer, Atif; Antonarakis, Emmanuel S; Stearns, Vered; Wolff, Antonio C; Feiweier, Thorsten; Kamel, Ihab R; Wahl, Richard L; Pan, Li (Academic radiology, 2018)
The purpose of this study was to investigate the use of multiparametric, whole-body, diffusion-weighted imaging (WB-DWI) and apparent diffusion coefficient (ADC) maps with T -weighted magnetic resonance imaging (MRI) at 3T for the detection and monitoring of metastatic disease in patients. Fifty-four participants (32 healthy subjects and 22 patients) were scanned with WB-DWI methods using a 3T MRI scanner. Axial, sagittal, or coronal fat-suppressed T -weighted (T WI), T -weighted (T WI), and DWI images were acquired. Total MRI acquisition and set-up time was approximately 45 minutes. Metastatic disease on MRI was confirmed based on T WI characteristics. The number of lesions was established on computed tomography (CT) or positron emission tomography (PET-CT). Whole-body ADC maps and T WI were constructed, and region-of-interests were drawn in normal and abnormal-appearing tissue for quantitative analysis. Statistical analysis was performed using a paired t tests and P < .05 was considered statistically significant. There were 91 metastatic lesions detected from the CT or PET-CT with a missed recurrent lesion in the prostate. Multiparametric WB-MRI had excellent sensitivity (96%) for detection of metastatic lesions compared to CT. ADC map values and the ADC ratio in metastatic bone lesions were significantly increased (P < .05) compared to normal bone. In soft tissue, ADC map values and ratios in metastatic lesions were decreased compared to normal soft tissue. We have demonstrated that multiparametric WB-MRI is feasible for oncologic staging to identify bony and visceral metastasis in breast, prostate, pancreatic, and colorectal cancers. WB-MRI can be tailored to fit the patient, such that an "individualized patient sequence" can be developed for a comprehensive evaluation for staging and response during treatment.